Determinants of Islamic Banking Profitability: A Cross-Country Panel Analysis from IFSB Data (2016-2024) - Maulida, Syahdatul (Department of Islamic Financial Management, Faculty of Economics and Islamic Business, Sunan Kalijaga State Islamic University, Yogyakarta, Indonesia., 2025)
Background: Islamic banking plays a crucial role in promoting financial inclusion and economic stability across member countries of the Islamic Financial Services Board (IFSB). However, the variability in profitability across nations raises questions regarding which internal financial factors most strongly influence performance at the industry level. Objectives: This study aims to analyze the influence of CAR, NPF, CIR, and LR on the ROA of Islamic banking industries across twelve IFSB member countries during 2016-2024. Novelty: This study provides a cross-country industry-level analysis of Islamic banking profitability, revealing that efficiency and credit risk management are stronger determinants of performance than capital strength. Research Methodology / Design: This research employs panel data regression using secondary data from IFSB. The sample includes 12 countries with consistent financial reporting from 2016–2024. Findings: The results reveal that NPF and CIR have significant negative effects on profitability, while LR has a significant positive effect. CAR shows a positive but statistically insignificant relationship. Implication: Theoretically, the study reinforces the efficiency and risk management theories within Islamic financial systems. Practically, regulators should prioritize policies enhancing operational efficiency and credit risk governance, while banks should optimize liquidity without compromising profitability sustainability.